À propos de Christian dit de Stavelot et son explication de I'évangile selon Matthieu - Huygens, R. B. C. (Sacris erudiri, 2005)
Ever since the publication of a pioneering study by Ernst Dümmler in the Berlin Sitzungsberichte of 1890, the commentary on the Gospel according to St Matthew by Christian, a teacher at the Benedictine abbey of Stavelot-Malmedy, has continuously attracted a great deal of interest. With the exception of only a few scholars, who had access to a manuscript, most others had to base their studies on Migne, PL 106, cols. 1261-1504. That text reproduces the editio princeps of 1514, which was produced by the well-known humanist Jakob Wimpfeling in Strasburg. In his much-used work De scriptoribus eccksiasticis Sponheim's famous abbot Trithemius first mentions another name by which Christian was to become known, viz. Druthmar(us). Though occasionally adopted by authors and compilers of catalogues of manuscripts, this other name was more generally assumed to have been imagined by Trithemius himself; but although it certainly is not authentic, it really does appear in a 15th-c. manuscript he may well have perused. A new edition is now being prepared for the Continuatio Mediaevalis, based on no fewer than nine manuscripts and two ancient editions (1514 and 1530, both representing supposedly lost manuscripts), and since the commentary must have been written around 865, it is of no small interest that the oldest of all these hitherto unused manuscripts (W, in Wolfenbüttel) dates back to as early as the late 9th c. — a fact that, unfortunately, has not prevented the archetype from being of a rather poor quality. The article summarised here, after dealing with the manuscript transmission of the text, concludes with an edition of Christian's dedicatory letter to the monks of Stavelot-Malmedy and the list of 77 rubrics (the latter lacking in Migne), based on all available textual witnesses.